2019
DOI: 10.1002/hyp.13636
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of soil moisture products from microwave remote sensing, land model, and reanalysis using global ground observations

Abstract: High-quality soil moisture (SM) datasets are in great demand for climate, hydrology, and other fields, but detailed evaluation of SM products from various sources is scarce. Thus, using 670 SM stations worldwide, we evaluated and compared SM products from microwave remote sensing [Advanced Microwave Scanning Radiometer for the Earth Observing System (AMSR-E) (C-and X-bands) and European Space Agency's Climate Change Initiative (ESA CCI)], land surface model [Global Land Data Assimilation System (GLDAS)], and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 72 publications
4
23
0
Order By: Relevance
“…During weak monsoon conditions, ERAI overestimates SM over India, and SM correlates well with observed rainfall (Shrivastava et al, 2017). Using 670 SM stations worldwide, Deng et al (2020) found that NCEP performed poorly in December-February and June-August and in arid or temperate and dry climates.…”
Section: Introductionmentioning
confidence: 77%
“…During weak monsoon conditions, ERAI overestimates SM over India, and SM correlates well with observed rainfall (Shrivastava et al, 2017). Using 670 SM stations worldwide, Deng et al (2020) found that NCEP performed poorly in December-February and June-August and in arid or temperate and dry climates.…”
Section: Introductionmentioning
confidence: 77%
“…Compared with ERA-Interim, the ERA5 4D-Var data assimilation system in the Integrated Forecasting System (IFS Cycle 41r2) has been improved with several modifications, representing a decade of research and development in modeling and data assimilation. The ERA soil moisture dataset was validated against the available data from multiple sources, and the use of this dataset for testing model simulations on daily to seasonal time scales has been confirmed [40,41]. In this study, we used the ERA5 soil moisture data from 1982 to 2015, and the depths of the four soil layers ranged from 0 to 7, 7-28, 28-100, and 100-289 cm, respectively.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Based on in situ SM observations, a variety of SM products have been evaluated at global and continental scales (e.g., Europe, North America, Southeast Asia, Australia, and Africa; Agrawal & Chakraborty, 2020; Albergel et al., 2012; Al‐Yaari et al., 2019; Bazzi et al., 2019; Beck et al., 2021; Das et al., 2019; Deng et al., 2020; Ford & Quiring, 2019; Griesfeller et al., 2013; Ray et al., 2017). A large number of metrics have been used in these studies to describe the ability of products to capture spatial patterns and temporal variability, such as the correlation coefficient, standard deviation, bias, root mean square error, and unbiased root mean square error.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, SM is profoundly influenced by precipitation, which is an important climatic factor. Their interrelationships and feedbacks are an integral part of hydrometeorology and water resources management (Deng et al., 2020). The study about the consistency between SM characterized by various products and precipitation is of significance for product comparison and further selection.…”
Section: Introductionmentioning
confidence: 99%